2005
DOI: 10.1111/j.1365-2958.2005.04974.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for siderophore‐dependent iron acquisition in group B streptococcus

Abstract: Summary Mutagenesis of group B streptococcus (GBS) withTn phoZ , a transposon designed to identify secreted protein genes, identified the gene homologues fhuD and fhuG . The encoded proteins participate in siderophore (hydroxamate)-dependent iron(III) transport in other bacterial species. Sequence analysis of the genome determined that fhuD and fhuG are members of a polycistronic operon comprised of four genes, fhuCDBG , that encode a putative ATPase, cell surface receptor and two transmembrane proteins respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…The structure of E. coli FhuD with loaded substrate has been resolved at the atomic level and reveals recognition of the ferric hydroxamate center. Distinct structures are observed in substrate-loaded FhuD proteins com- (36), and a group B streptococcus (12). The fhuD fhuB fhuG fhuC genes of S. pneumoniae are transcribed in the same direction and most likely form an operon.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The structure of E. coli FhuD with loaded substrate has been resolved at the atomic level and reveals recognition of the ferric hydroxamate center. Distinct structures are observed in substrate-loaded FhuD proteins com- (36), and a group B streptococcus (12). The fhuD fhuB fhuG fhuC genes of S. pneumoniae are transcribed in the same direction and most likely form an operon.…”
Section: Discussionmentioning
confidence: 96%
“…In the following, spr0934 will be designated fhuD, spr0935 fhuB, spr0936 fhuG, and spr0938 fhuC, (Fig. 3B) according to the nomenclature introduced by Clancy et al (12), who studied siderophore-dependent iron acquisition of a group B streptococcus. We refrained from using the pia gene nomenclature introduced by Brown et al (9) because the fhu designation specifically refers to ferric hydroxamate uptake, which we introduced for E. coli (26) and has been used since then for gram-negative and gram-positive bacteria (5,8,30,31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clancy et al (4) have now reported a siderophore (hydroxamate)-mediated iron transport system in GBS characterized by a FhuD siderophore receptor localized to the cell membrane. A polycistronic operon of four genes (fhuCDBG) putatively encodes an ATPase, cell surface receptor, and two transmembrane proteins, respectively (4).…”
Section: Vol 75 2007 Transcriptional and Proteomic Profiles Of Gbs mentioning
confidence: 99%
“…Interestingly, the putative ferrichrome transporter genes (SMU.995 to SMU.998) were induced in the ⌬rpoE strain under every condition, except to a smaller degree under oxidative stress. Sufficient levels of iron are necessary for bacterial survival and growth, but the accumulation of iron can lead to the production of toxic oxygen radicals via Fenton chemistry (17,76). Thus, its intracellular transport must be tightly controlled, and such induction might cause toxicity to the ⌬rpoE strain.…”
Section: Vol 192 2010 Rpoe Is a Global Modulator In Streptococcus Mmentioning
confidence: 99%